2016
DOI: 10.1158/0008-5472.can-16-1545
|View full text |Cite
|
Sign up to set email alerts
|

Cardiolipins Are Biomarkers of Mitochondria-Rich Thyroid Oncocytic Tumors

Abstract: Oncocytic tumors are characterized by an excessive eosinophilic, granular cytoplasm due to aberrant accumulation of mitochondria. Mutations in mitochondrial DNA occurs in oncocytic thyroid tumors, but there is no information about their lipid composition which might reveal candidate theranostic molecules. Here we used desorption electrospray ionization mass spectrometry (DESI-MS) to image and chemically characterize the lipid composition of oncocytic thyroid tumors, as compared to non-oncocytic thyroid tumors … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 39 publications
5
72
0
Order By: Relevance
“…The mass spectra obtained in the negative ion mode for each tissue type presented a rich variety of molecular ions commonly observed from human tissues by DESI-MSI (18), with high relative abundances of metabolites, FA, and complex lipids. For example, the mass spectra obtained for PTC tissue sections presented lipid species previously identified as diagnostic markers by DESI-MSI (27), including a variety of doubly charged CL and other GL such as PI(38:4) ( m/z 885.550), PI(36:4) ( m/z 857.518), PE(38:4) ( m/z 766.539), and PE (36:2) ( m/z 742.539) (table S2). A distinct mass spectral profile was obtained for the normal thyroid tissue sections, presenting high relative abundances of iodine ( m/z 126.904), glutamine ( m/z 145.050), ascorbic acid ( m/z 175.024), C 36 H 78 O 9 N 3 I (tentatively assigned; m/z 822.472), and PI(38:4) ( m/z 885.551) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The mass spectra obtained in the negative ion mode for each tissue type presented a rich variety of molecular ions commonly observed from human tissues by DESI-MSI (18), with high relative abundances of metabolites, FA, and complex lipids. For example, the mass spectra obtained for PTC tissue sections presented lipid species previously identified as diagnostic markers by DESI-MSI (27), including a variety of doubly charged CL and other GL such as PI(38:4) ( m/z 885.550), PI(36:4) ( m/z 857.518), PE(38:4) ( m/z 766.539), and PE (36:2) ( m/z 742.539) (table S2). A distinct mass spectral profile was obtained for the normal thyroid tissue sections, presenting high relative abundances of iodine ( m/z 126.904), glutamine ( m/z 145.050), ascorbic acid ( m/z 175.024), C 36 H 78 O 9 N 3 I (tentatively assigned; m/z 822.472), and PI(38:4) ( m/z 885.551) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the molecular model built by the Lasso to discriminate between HGSC and healthy tissue (Supplemental Table 3) pinpointed additional GP markers such as CL. Positive weights were assigned to CL 72:8 and CL 72:7 to characterize HGSC, suggesting a role for these lipids in tumor growth and proliferation (32). In the positive ion mode, several PC species were selected as predictive markers.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, several PG and PI species were identified as predictive markers for tumor aggressiveness, with increased relative abundance in HGSC samples. CLs, which are complex GP species present almost exclusively in the inner mitochondrial membrane, were also observed in increased relative abundances in HGSC tissue when compared to normal tissue (32). Moreover, increased relative abundances of ubiquinone, a component of the mitochondrial respiratory chain, was also found to be characteristic of serous ovarian tumors (37).…”
Section: Discussionmentioning
confidence: 99%
“…Gerbig et al systematically segregated colorectal adenocarcinoma tissue area from healthy intestine mucosa and smooth muscle tissue using DESI‐MSI with the aid of PCA/LDA statistical tool, as illustrated in Figure A . Oncocytic thyroid tumours and non‐oncocytic thyroid tumours were investigated in 45 tissue specimens using DESI‐MSI along with significance analysis of microarrays (SAM) statistical tool . Cardiolipins were identified as critical biomarkers for thyroid cancer with higher SAM contrast values for monolysocardiolipins [MLCL (54:5)], oxidized CL (18:2/18:2/18:2/9:1(OOH)), CL (18:2/18:2/18:2/18:1), CL (20:4/18:2/18:2/18:1) and CL + PC (108:9) in oncocytic tumor tissue than in non‐oncocytic tumor tissue and normal tissue.…”
Section: Recent Applications In Ambient Ms Imagingmentioning
confidence: 99%
“…95 Oncocytic thyroid tumours and non-oncocytic thyroid tumours were investigated in 45 tissue specimens using DESI-MSI along with significance analysis of microarrays (SAM) statistical tool. 96 accurate identification of meningioma tissue margins. 98 Psychiatric disorders such as schizophrenia, 99 Parkinson's and Alzheimer's were also studied by ambient MS to characterize and map critical metabolites pertaining to these neurological diseases.…”
Section: Other Rare Cancers and Diseased State Tissuesmentioning
confidence: 99%